2019
DOI: 10.1097/md.0000000000017652
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative intestinal tuberculosis case as a complication of treatment by infliximab for intestinal Behçet's disease

Abstract: Rationale:Intestinal Behçet's disease (BD) is characterized by intestinal ulcerations and gastrointestinal symptoms. Ulcerative intestinal tuberculosis (TB) is usually with dyspepsia, abdominal pain, vomiting, and weight loss. The 2 diseases exhibit similar clinical manifestations, but the most critical aspects of their clinical courses and required treatments are not at all similar.Patient concerns:We present a case in which a patient with intestinal Behçet's disease developed a de novo ulcerative intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…As both BD and TB infection are common diseases in Turkey, TB data among TNF- antagonist treated patients deserve separate analysis. Apart from Turkey, a few case reports have been published in the literature on BD and TB coexistence [15][16][17][18]. In the series from Turkey, Kısacık et al showed that TB development rate was higher in BD compared to other rheumatic diseases (5/129, 4%).…”
Section: Discussionmentioning
confidence: 99%
“…As both BD and TB infection are common diseases in Turkey, TB data among TNF- antagonist treated patients deserve separate analysis. Apart from Turkey, a few case reports have been published in the literature on BD and TB coexistence [15][16][17][18]. In the series from Turkey, Kısacık et al showed that TB development rate was higher in BD compared to other rheumatic diseases (5/129, 4%).…”
Section: Discussionmentioning
confidence: 99%
“…En áreas donde la tuberculosis y la EB son endémicas, se cree necesario considerar la tuberculosis intestinal como diagnóstico diferencial. Ya que, además de una sintomatología similar y afinidad por la región ileocecal, sus tratamientos difieren sustancialmente (2,33) . Y, para colmo, se han reportado casos de tuberculosis intestinal como complicación de la terapia biológica para EB, siendo entonces un diferencial a tener en cuenta tanto al momento del diagnóstico como en el seguimiento (33) .…”
Section: Diagnóstico Diferencialunclassified
“…Ya que, además de una sintomatología similar y afinidad por la región ileocecal, sus tratamientos difieren sustancialmente (2,33) . Y, para colmo, se han reportado casos de tuberculosis intestinal como complicación de la terapia biológica para EB, siendo entonces un diferencial a tener en cuenta tanto al momento del diagnóstico como en el seguimiento (33) . Dentro de las ayudas para diferenciar ambas entidades están la ausencia de compromiso extra intestinal en TB, la presencia de TB diseminada o pulmonar en el 50% de los casos, la presencia de fiebre (aunque no excluye EB debe hacer pensar como primera opción en TB) (6,34) .…”
Section: Diagnóstico Diferencialunclassified